2022
DOI: 10.1021/acssuschemeng.1c05737
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Switchable Phase Separation of Nonaqueous Surfactant-Free Ionic Liquid-Based Microemulsions

Abstract: Surfactant-free microemulsions (SFMEs) have shown great potential in many aspects such as chemical reactions and material preparation. Ionic liquid (IL)-based SFME is a promising member in this family. However, switchable phase separation of nonaqueous IL SFMEs has not been reported up to now although it is of great importance for the separation of products and recycling of the systems. Herein, a new kind of CO2-responsive SFMEs composed of quaternary ammonium IL, dimethyl sulfoxide, and ethyl acetate has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…According to their high-resolution XPS spectra, the binding energies at approximately 179.2 and 181.5 eV were ascribed to Zr 3d 5/2 and Zr 3d 3/2 (Figure S1a), respectively, which indicated the presence of Zr 4+ for the zirconium-oxo cluster. 53 Three main peaks of C 1s at 284.8, 286.5, and 288.9 eV belonged to C−C/C�C, C−N, and C� O 54 (Figure S1b), respectively. The structure spectrum of N 1s showed two peaks at 398.4 and 400.1 eV (Figure 2b), indicating the existence of C−N and N−H bonds, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…According to their high-resolution XPS spectra, the binding energies at approximately 179.2 and 181.5 eV were ascribed to Zr 3d 5/2 and Zr 3d 3/2 (Figure S1a), respectively, which indicated the presence of Zr 4+ for the zirconium-oxo cluster. 53 Three main peaks of C 1s at 284.8, 286.5, and 288.9 eV belonged to C−C/C�C, C−N, and C� O 54 (Figure S1b), respectively. The structure spectrum of N 1s showed two peaks at 398.4 and 400.1 eV (Figure 2b), indicating the existence of C−N and N−H bonds, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…4a, two new signals at 160.4 and 164.5 ppm appeared and belonged to bicarbonate and carbamate, respectively, which indicated the generation of hydrophilic ammonium salts. 28,29 Moreover, the two signals disappeared after removal of CO 2 , proving that the reaction process is perfectly reversible.…”
mentioning
confidence: 93%
“…CO 2 is abundant, nonhazardous, inexpensive and nonaccumulating in the system and can be utilized as a trigger for many switching processes. 28,29 Here, for the first time, we prepared a new kind of CO 2 -switchable functionalized ZIF-90 by the covalent post-modification of ZIF-90 with diamines and investigated its phase transfer behavior between organic and aqueous solutions. It was observed that the aminefunctionalized ZIF-90 was initially well dispersed in the organic phase.…”
mentioning
confidence: 99%
“…[31][32][33] Recently, nonaqueous ionic liquid based microemulsions have been investigated as ion-conductive electrolytes. [34][35][36][37] However, they have not been applied for LMBs primarily due to their weak mechanical strength.…”
Section: Introductionmentioning
confidence: 99%